1994
DOI: 10.1002/apmc.1994.052170110
|View full text |Cite
|
Sign up to set email alerts
|

Transesterification in blends of poly(butylene terephthalate) and bisphenol‐A‐polycarbonate

Abstract: By means of differential calorimetric and X-ray examinations it was shown that poly(buty1ene terephthalate) (PBT) and bisphenol-A-polycarbonate (PC) are only compatible in the melt if they stay in the melt for a short period of time. During mixing in the melt, transesterification begins and block copolymers are formed. A characteristic glass transition temperature is observed for each individual blend. Butylene terephthalate (BT)-blocks are crystallizable; however, with an increasing share of bisphenol-A-carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The reactions that can occur in this system are summarised in Scheme la-c. The exchange reaction between high MW PBT and PC, ie., containing non-detectable amounts of reactive end-groups, occurs even at 240°C in the presence of an esterification catalyst, by an inner-inner mechanism (Scheme la) [4][5][6][7][8][9][10][11][12][13]401. To explore the dependence of the copolymer composition on the inner-inner exchange mechanism, we have reacted an equimolar mixture of high MW PBT and PC at 240°C in the presence of Ti(OBu)4, in a Brabender mixer for different times [40].…”
Section: Capped Pbt/pc Blendsmentioning
confidence: 99%
“…The reactions that can occur in this system are summarised in Scheme la-c. The exchange reaction between high MW PBT and PC, ie., containing non-detectable amounts of reactive end-groups, occurs even at 240°C in the presence of an esterification catalyst, by an inner-inner mechanism (Scheme la) [4][5][6][7][8][9][10][11][12][13]401. To explore the dependence of the copolymer composition on the inner-inner exchange mechanism, we have reacted an equimolar mixture of high MW PBT and PC at 240°C in the presence of Ti(OBu)4, in a Brabender mixer for different times [40].…”
Section: Capped Pbt/pc Blendsmentioning
confidence: 99%
“…In recent years considerable interest has arisen in the study of the exchange reactions which may occur during the melt mixing processes of polymers containing reactive functional groups (ester, carbonate, amide, etc. ). …”
Section: Introductionmentioning
confidence: 99%
“…End-group-activated exchange, or catalyst-activated exchange, may occur in such systems below 300 °C, whereas both thermal activated exchange (i.e., without catalysts) and thermal decomposition occur above 300 °C. ,,, …”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that PBT/PC blends are immiscible 13,[18][19][20][21] or partially miscible 5,22,23 at the T g level as multiphase materials. More importantly, investigations have shown that PC can hinder PBT crystallization in PBT/PC blends 24,25 .…”
Section: Dsc Analysismentioning
confidence: 99%